Rivulet: Exploring Participation in Live Events through Multi-Stream Experiences (Best Paper Award) - Hamilton, William A.; Tang, John; Venolia, Gina; Inkpen, Kori; Zillner, Jakob; Huang, Derek (TVX 2016, 2016)
Live streaming has recently emerged as a growing form of participatory social media. While current live streaming practice focuses on single stream experiences, there are increasing instances of events covered by multiple live streams. In order to explore how to support communication and participation in multi-stream experiences, we present the design and evaluation of Rivulet, an end-to-end mobile live streaming system designed to support participatory multistream experiences. Rivulet affords simultaneously watching multiple live streams and incorporates existing feedback mechanisms of text chat and hearts with a novel push-to-talk audio modality. By recruiting viewers through Mechanical Turk, we were able to conduct a study of Rivulet at scale. We found that Rivulet afforded new engaging experiences for participants and led to an impromptu sense of community.
Best Paper